Current issues in diagnosis and treatment of von Willebrand disease - Keesler, Daniel A. (Res Pract Thromb Haemost, 2017)
ESSENTIALS: Classification of VWD includes quantitative (types 1 and 3) and qualitative (type 2) variants. New assays of VWF‐platelet binding may improve accuracy in diagnosis. Collagen binding represents an additional function of VWF not measured by current tests. Treatment options for VWD include desmopressin, plasma‐derived, and recombinant VWF. Clinically, von Willebrand disease (VWD) presents as mucosal bleeding caused by a decreased quantity or quality of von Willebrand factor (VWF). Diagnosis of VWD requires careful consideration of patient specific factors, bleeding symptoms, and laboratory results. Patients with borderline low VWF levels remain challenging, given that low VWF is not necessarily a guarantee of bleeding, but is present in many patients with symptoms, and treatment of low VWF may improve bleeding. Laboratory diagnosis of VWD is complex and no single test can determine the presence or absence of functional VWF. Historically, VWF binding to platelet GPIbα was measured by the ristocetin cofactor assay (VWF:RCo); a new assay using platelet GPIbα in the absence of ristocetin (VWF:GPIbM) is gradually replacing the VWF:RCo due to improved accuracy in diagnosis. VWF binding to collagen is a separate function, and requires specific testing to determine if a collagen binding defect is present. Regardless of these laboratory complexities, clinicians can empirically treat VWD to alleviate bleeding symptoms by raising VWF levels through desmopressin or VWF concentrate. Recombinant VWF is now available, but clinicians may need to add an initial dose of FVIII when treating emergency bleeds.